A Novel Compound Heterozygous Mutation in ABCB4 Gene Leading to Cholelithiasis, Progressive Familial Intrahepatic Cholestasis (Type 3), and Cirrhosis in a Child - Mirza, Nida; Malhotra, Smita; Sibal, Anupam (Journal of Child Science, 2020)
Progressive familial intrahepatic cholestasis (PFIC) is a heterogeneous group of autosomal recessive disorders of childhood which presents with intermittent or progressive episodes of cholestasis, with jaundice and pruritus as most common presenting symptoms. PFIC type 3 occurs due to mutations in the ABCB4 gene, mutation in this gene has wide spectrum of features which include intrahepatic stones, cholelithiasis, PFIC type 3, and intrahepatic cholestasis of pregnancy. Here, we are reporting a peculiar case of young male adolescent with novel variant compound heterozygote missense mutation in ABCB4 gene who had gall stone as initial symptom, followed by symptoms of PFIC and eventually decompensated chronic liver disease.
Keywords: gallstone; novel mutation; liver cirrhosis